Implementasi Media Canva pada Pembelajaran IPA dan Pendekatan Deep Learning pada Pembelajaran Bahasa Inggris terhadap Motivasi Belajar Siswa SMP Negeri 3 Galesong Selatan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the simultaneous effect of implementing Canva, an interactive visual media, in Science (Ilmu Pengetahuan Alam/IPA) and the application of the Deep Learning approach (in-depth and contextual learning) in English on improving students' learning motivation at SMP Negeri 3 Galesong Selatan. Learning motivation is measured as a dependent variable crucial for academic success in the digital era. This research uses a Mixed Methods design with an embedded quasi-experimental model, supported by descriptive qualitative data through in-depth observations and interviews. The research sample consists of seventh-grade students who were the subjects of the Canva intervention in Science, and eighth-grade students who were the subjects of the Deep Learning intervention in English, each compared with a control group. The results of the paired t-test hypothesis test showed a significant and positive increase in students' learning motivation in both intervention groups. Qualitatively, Canva proved effective in visualizing complex Science concepts, facilitating understanding and creativity. Meanwhile, Deep Learning successfully contextualized English through authentic projects, enhancing material relevance and student independence. The main conclusion of this study is that the combination of visual technology innovation and the adoption of pedagogy focused on in-depth understanding is a transformative strategy for fostering strong intrinsic learning motivation at the junior high school level.